Starting the Study of Electronic Circuits with VISIR. College students’ viewpoints in a Pilot Test in Argentina - Marchisio, Susana (2018)
This paper aims at introducing the first intensive use of a remote lab named as VISIR by lecturers and students from Facultad de Ciencias Exactas, Ingeniería y Agrimensura, Universidad Nacional de Rosario. The research was carried under the VISIR + project. It is a pilot test in which 17 students from the third year of an Electronic Engineering degree took part. The pilot test was developed in order to bring forward possible difficulties, assess successes and failures and eventually suggest other possible ways of curricular incorporation of VISIR in the teaching of the Physics of Electronic Devices subject. VISIR was used as a complement to hands-on lab, after the last experimental design activity of basic circuits with bipolar transistor. The students carried out an individual lab work. Then, they were asked to answer an opinion poll made up of 20 items, 1-4 Likert scale. Descriptive statistical analysis and summary of cases were carried out in order to conclude about four dimensions of analysis linked to the students’ viewpoint. They are: perceived learnings, VISIR acceptance, perceived teachers’ guidance and time and technical restrictions.